2007
DOI: 10.1007/s12263-007-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of vitamin E by induction of drug metabolism

Abstract: Observational studies with healthy persons demonstrated an inverse association of vitamin E with the risk of coronary heart disease or cancer, the outcome of large-scale clinical trials conducted to prove a benefit of vitamin E in the recurrence and/or progression of such disease, however, was disappointing. Vitamin E did not provide benefits to patients with cardiovascular diseases, cancer, diabetes or hypertension. Even harmful events and worsening of pre-existing diseases were reported, which are hard to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 83 publications
0
30
0
1
Order By: Relevance
“…Vitamin E has been promoted as a strategy to prevent atheroscleosis, cardiovascular disease and cancer due to its properties such as inhibition of oxidation and inflammation, increasing release of prostacyclin, promoting blood vessel dilatation and reducing platelet aggregation [5,41]. There are, however, conflicting results on the benefit of vitamin E in the recurrences and/or progression of such diseases, and even worsening of pre-existing diseases, which is hypothesized to be due to interactions of vitamin E and the drug-metabolizing system, has been reported [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E has been promoted as a strategy to prevent atheroscleosis, cardiovascular disease and cancer due to its properties such as inhibition of oxidation and inflammation, increasing release of prostacyclin, promoting blood vessel dilatation and reducing platelet aggregation [5,41]. There are, however, conflicting results on the benefit of vitamin E in the recurrences and/or progression of such diseases, and even worsening of pre-existing diseases, which is hypothesized to be due to interactions of vitamin E and the drug-metabolizing system, has been reported [42]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Brigelius-Floh [5] indicated that vitamin E does not always have beneficial effect on some of diseases such as cardiovascular diseases, cancer, diabetes and hypertension. Moreover, vitamin E in combination with the initiators azo compounds, Cu 2+ , was reported to enhance oxidation of human low density lipoproteins [1][2][3][4].…”
Section: Vitamin Ementioning
confidence: 99%
“…Moreover, vitamin E in combination with the initiators azo compounds, Cu 2+ , was reported to enhance oxidation of human low density lipoproteins [1][2][3][4]. These findings showed that the initiators are required for induction of vitamin E pro-oxidant activity [1][2][3][4][5].…”
Section: Vitamin Ementioning
confidence: 99%
“…La activación de estos citocromos transforma al α-tocoferol en carboetil-1-hidroxicromano (CEHC), el que es conjugado con ácido glucurónico. El exceso de CEHC activa la expresión de enzimas que metabolizan drogas que se utilizan en la quimioterapia de pacientes cancerosos, con lo cual disminuye drásticamente la efectividad de dichas drogas (78).…”
Section: Vitaminasunclassified